DETERMINANTS OF STUDENTS’ RELIGIOUS MODERATION IN INDONESIAN ISLAMIC HIGHER EDUCATION: A CONFIRMATORY FACTOR ANALYSIS APPROACH - Qomusuddin, Ivan Fanani; Latifah, Siti; Erihadiana, Mohamad (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
Religious moderation has become a central issue in Indonesia’s pluralistic religious landscape, where differences in faith and cultural traditions coexist within a shared national framework. Among university students, however, the understanding and application of moderation values remain uneven, as indicated by challenges such as the rise of intolerant attitudes and limited opportunities for constructive intergroup dialogue. This study seeks to examine the level of religious moderation among students and to identify the most significant factors that influence its formation within the context of Islamic higher education. The research employed a quantitative design using a survey of 95 students at STIT At-Taqwa Ciparay Bandung. The instrument measured four core dimensions of religious moderation: national commitment, tolerance, anti-violence, and accommodation to local culture. Data were analyzed using Confirmatory Factor Analysis (CFA) with the assistance of Lisrel 8.8 software. The results indicate that students’ religious moderation is at a moderate level, suggesting a reasonably good foundation while highlighting the need for reinforcement in specific areas. More importantly, several indicators recorded high loading factor values, namely cooperation, empathy, openness, and acceptance of differences. These findings reveal that interpersonal and relational attitudes play a pivotal role in shaping moderate religious orientations. The study concludes that strengthening these high-loading factors, alongside the four main dimensions, can significantly enhance students’ capacity to internalize and practice religious moderation, thereby supporting a more harmonious and inclusive educational environment. AbstrakModerasi beragama telah menjadi isu sentral dalam lanskap keagamaan yang pluralistik di Indonesia, di mana perbedaan keyakinan dan tradisi budaya hidup berdampingan dalam bingkai kebangsaan. Namun, di kalangan mahasiswa, pemahaman dan penerapan nilai-nilai moderasi masih belum merata, yang ditunjukkan oleh munculnya sikap intoleran serta terbatasnya ruang dialog antar kelompok. Penelitian ini bertujuan untuk mengkaji tingkat moderasi beragama mahasiswa serta mengidentifikasi faktor-faktor signifikan yang memengaruhi pembentukannya dalam konteks perguruan tinggi Islam. Penelitian menggunakan desain kuantitatif dengan survei terhadap 95 mahasiswa STIT At-Taqwa Ciparay Bandung. Instrumen penelitian mengukur empat dimensi inti moderasi beragama, yaitu komitmen kebangsaan, toleransi, anti-kekerasan, dan akomodasi terhadap budaya lokal. Data dianalisis dengan Confirmatory Factor Analysis (CFA) menggunakan perangkat lunak Lisrel 8.8. Hasil penelitian menunjukkan bahwa tingkat moderasi beragama mahasiswa berada pada kategori sedang, yang mencerminkan dasar pemahaman dan penerapan nilai-nilai moderasi yang cukup baik, namun masih memerlukan penguatan di beberapa aspek. Lebih jauh, beberapa indikator ditemukan memiliki nilai loading factor tinggi, yaitu kerja sama, empati, keterbukaan, dan penerimaan terhadap perbedaan. Temuan ini menegaskan bahwa sikap interpersonal dan relasional berperan penting dalam membentuk orientasi keagamaan yang moderat. Penelitian ini menyimpulkan bahwa penguatan faktor-faktor dengan loading tinggi, bersamaan dengan penguatan empat dimensi utama, dapat secara signifikan meningkatkan kapasitas mahasiswa dalam menginternalisasi dan mempraktikkan moderasi beragama, sehingga mendukung terciptanya lingkungan pendidikan yang harmonis dan inklusif.